What should we do to optimise outcome in twin pregnancy complicated with placenta percreta? A case report. Issue 1 (December 2015) - Atalay, Mehmet; Oz Atalay, Fatma; Cetinkaya Demir, Bilge
Abstract Background Patients with morbidly adherent placenta (MAP) are under risk of massive bleeding. It readily necessitates very complicated surgery and massive blood transfusion, and even leads to mortality. Cesarean hysterectomy (CH) is the procedure that is acknowledged worldwide, since it helps to minimize complications. Case presentation A patient with dichorionic twin pregnancy underwent to cesarean section (CS) due to preliminary diagnosis of placenta percreta at her 35th week of pregnancy. Both of the placentas were left in situ. The patient admitted with signs of infection. Emergency total abdominal hysterectomy was performed 7 weeks after CS. In the course of hysterectomy, 3 units of erythrocyte suspension and 2 units of fresh frozen plasma were transferred, whereas none was required during CS. Conclusion Abandoning placenta in situ seems to be a logical alternative to the CH in patients with placenta percreta in order to minimize complications related to massive blood transfusion and surgical technique. However, it appears to increase maternal morbidity due to maternal infection in twin pregnancy.